The Capability Of The Third Year Students Of Smp N 2 Panekan Magetan In Understanding Written Texts - ASMARA, RINA WAHYU (2012)
The objectives of this study are (1) to describe the capability of the third year students of SMP N 2 Panekan Magetan in understanding written texts, (2) to describe the problems faced by the third year students in understanding written texts, and (3) to describe the causes of problems faced by the third year students in understanding written texts. The study was done in SMP N 2 Panekan Magetan. As the sample , the writer took the students in class IX A with 27 students in that class. The writer conducted treatment to the students in the form of the test. The type of test is multiple choice with four options and consists of 50 items. After collecting the data and analyzing using the formula, the writer described the result of the study. The writer found that the capability of the students in understanding written texts can be divided into four levels of mastery, namely (1) poor level is 14. 81 % (4 students), (2) fair level is 29.63 % (8 students), (3) good level is 48.15 % (13 students), and (4) excellent level is 7.41 % (2 students). The problems faced by the students in understanding written texts are (1) understanding the statement of exception, and (2) understanding moral value. The causes of the problems faced by the students are (1) they seldom read English texts, (2) lack of vocabulary, (3) they seldom read the dictionary, (4) they rarely pronounce English words in daily life, while the difficulties caused by the teacher are (1) the teacher does not use various books in teaching reading, (2) the teacher has not used multimedia facilities, and (3) the methods implemented by the teacher. Conclusion, the capability of the third year students of SMP N 2 Panekan Magetan in understanding written texts is good.